Therapeutic architecture and spatial perception in the environments of a Mental Health Center - Lopez-Rodriguez, Angie Susana; Bustamante-Guado, Guillermo Alberto; Cruzado-Palacios, María Delia (LACCEI, 2025)
In the design of spaces for mental health, therapeutic architecture plays a fundamental role in the perception and well-being of users. Understanding this relationship allows generating environments that promote recovery and emotional comfort. The objective of this research is to analyze the relationship between therapeutic architecture and spatial perception in the environments of the mental health center "Psiconstruye" in the district of Chimbote. The methodology adopted is a mixed approach, with a correlational scope and a design based on case studies. Case analysis and observation techniques were used, applied to the different environments of the center, using registration forms as a data collection instrument. The results showed a significantly high correlation between therapeutic architecture and spatial perception in the mental health center "Psiconstruye", which allowed to base the development of a design proposal for the optimization of a specific environment.